Early Childhood Caries Prevalence, Severity and Pattern in 3-6 Year Old Preschool Children of Mysore City, Karnataka - Deepti AGARWAL (Pesquisa Brasileira em Odontopediatria e Clínica Integrada, 2012)
Objective: To determine Early Childhood Caries (ECC) prevalence, severity and pattern in preschool children of Mysore City, Karnataka. Methods: A total of 10 preschools, five government and five private were selected randomly from 5 different sectors in Mysore. A total of 500 children and their parents were included in the study. Early Childhood caries was diagnosed using NIDCR definition. Dental caries status was recorded using dmft and dmfs indices. Results: The results show that early childhood caries prevalence in 3-6 year old preschool children was 56.6% with a mean dmft and dmfs of 2.20 and 2.97 respectively. Out of the 500 children, 56% males and 57.1 % females were affected .There was no difference in caries prevalence between children of government and private preschools. 94.84% of total dmf was comprised of decayed component. Maxillary arch was affected more (29.32%) than the mandibular arch (26.14%).The most affected surfaces were the occlusal surfaces (46%) and least affected were the smooth surfaces (16%). Mandibular posteriors were affected the most (39.42%) and lower incisors were the least affected (1.84%). Conclusion: The results support the view that oral counseling should begin within 6 months of eruption of 1st primary tooth.